SHARENTING IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Fitria Fauziah Hasanah (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
This article discusses “sharenting” (sharing representations of one’s parenting or children online) in the perspevtive of Islamic education. The term “sharenting”, coined from “share” and “parenting”, When parents share information about their children online, they do so without their children’s consent. Lack of legal regulations regarding the protection of children’s privacy online was also pointed out. sharenting has become a subject of research by increasing numbers of scholars worldwide, but the knowledge of this phenomenon is still meagre. This Article explores potential legal solutions to this issue and offers a set of best practices for parents to consider when sharing about children online in the perspevtive of Islamic education that Sharenting must be done by parent by maintaingin four principles : Maintain the nature of children (al muhafazoh), Develop childrens potential (at tanmiyah), With clear directions (at taujih), and Gradually (at tadaruj).